The Economic Benefits of Marine Protected Areas - Oracion, Enrique G. (Silliman Journal, 2023)
This paper argues that no-take marine protected areas (MPAs) can be sustainable if they offer direct and indirect economic benefits to all members, especially fish-ing households which have been displaced from their traditional fishing grounds. A majority of the respondents of the study agreed that the existing MPAs have brought them a number of benefits. Direct benefit comes from improved fish catch brought about by MPA spillover effects and monetary incentives derived from user fees paid by tourist divers; indirect benefits include alternative livelihood assistance. Non-fishing members of fishers' associations who manage and enforce the MPAs as well as non-member fishers also enjoyed these benefits. The findings of this study show that proper financial management and appropriation of the income of fishers' associations is necessary to sustain the economic benefits of MPAs.